Comparing Single-Dose Versus Multi-Dose Benzathine Penicillin G for the Treatment of Late Latent Syphilis : A Systematic Review of Randomized Controlled Trials and Primary Studies - Rielyana Lumban Gaol (The Indonesian Journal of General Medicine, 2026)
Introduction: Late latent syphilis (LLS), defined as asymptomatic Treponema pallidum infection of >1 year duration, remains a global public health burden. Current guidelines recommend three weekly intramuscular (IM) doses of benzathine penicillin G (BPG) 2.4 million units (MU), yet adherence to this multi-dose regimen is suboptimal, and emerging evidence challenges its superiority over single-dose BPG. Methods: A systematic search adhered to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines from inception to June 2026. We included randomized controlled trials (RCTs), prospective and retrospective cohort studies, and systematic reviews comparing single-dose versus multi-dose BPG in adults with LLS or syphilis of unknown duration. Risk of bias was assessed using Cochrane RoB 2 and Newcastle-Ottawa Scale. Results: Twenty studies (N>25,000 subjects) were included. The landmark NEJM RCT (Hook et al., 2025; N=249) demonstrated single-dose BPG was non-inferior to three-dose BPG for serologic response at 6 months (76% vs 70%; difference −6 percentage points, 90% CI −15 to +3). A large retrospective US study (Pugsley et al., 2026; N=18,027) examining late/unknown-duration syphilis found 4-fold titer decrease rates of 80% (1 dose) versus 75% (3 doses) at 24 months (no significant difference). Adherence to three-dose regimens ranged from 45–78% versus near-complete adherence to single-dose therapy. Jarisch-Herxheimer reaction occurred in 23.7% after the first dose; injection-site pain was lower in the single-dose group (76% vs 85%). No clinical relapse or tertiary progression was documented. Discussion: Across RCT and real-world evidence, single-dose BPG demonstrates equivalent serological efficacy to three-dose BPG for LLS with superior adherence. Factors independently associated with non-response include older age, low baseline RPR titer, female sex, and HIV co-infection. Pharmacokinetic rationale for three doses is challenged by pharmacodynamic modeling showing sustained treponemicidal concentrations with single-dose formulations. The serofast state (21–41%) is not reduced by additional BPG doses. Conclusion: Current evidence indicates single-dose BPG 2.4 MU is non-inferior to three-dose BPG for late latent syphilis regarding serological and clinical outcomes, with substantial advantages in adherence and tolerability. Guideline-revision bodies should consider revising treatment standards pending confirmatory RCT data in exclusively late latent populations.